2023
DOI: 10.3389/fnagi.2023.1007436
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture on mild cognitive impairment: A systematic review of neuroimaging studies

Abstract: Mild cognitive impairment (MCI) is a multifactorial and complex central neurodegenerative disease. Acupuncture appears to be an effective method for cognitive function improvement in MCI patients. Neural plasticity remaining in the MCI brain implies that acupuncture-associated benefits may not be limited to the cognitive function. Instead, neurological alternations in the brain play a vital role in corresponding to the cognitive improvement. However, previous studies have mainly focused on the effects of cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Multiple systematic reviews and meta-analyses of randomized controlled trials [16,59,60] have shown that acupuncture can effectively promote the rehabilitation of patients with cognitive impairment after cerebral infarction and improve their scores on the Mini-Mental State Examination, the Montreal Cognitive Assessment, and Hasegawa Dementia Scale. In a systematic review [61] of 22 studies (with a total of 647 patients) that used neuroimaging to investigate the therapeutic mechanisms of acupuncture for mild cognitive impairment, researchers found that the cingulate cortex, hippocampus, and prefrontal cortex were the 3 brain regions most influenced by acupuncture. However, the correlation between brain responses and clinical outcomes remains to be investigated.…”
Section: Research Hotspotsmentioning
confidence: 99%
“…Multiple systematic reviews and meta-analyses of randomized controlled trials [16,59,60] have shown that acupuncture can effectively promote the rehabilitation of patients with cognitive impairment after cerebral infarction and improve their scores on the Mini-Mental State Examination, the Montreal Cognitive Assessment, and Hasegawa Dementia Scale. In a systematic review [61] of 22 studies (with a total of 647 patients) that used neuroimaging to investigate the therapeutic mechanisms of acupuncture for mild cognitive impairment, researchers found that the cingulate cortex, hippocampus, and prefrontal cortex were the 3 brain regions most influenced by acupuncture. However, the correlation between brain responses and clinical outcomes remains to be investigated.…”
Section: Research Hotspotsmentioning
confidence: 99%
“…Acupuncture was safe and effective for MCI when used as an alternative or adjunctive treatment compared with that observed when sham acupuncture, medication, and usual care were used as treatment (12)(13)(14)(15)(16). A systematic review of neuroimaging studies revealed that acupuncture may have an effect on the regulation of the central executive network, salience network, and default mode network, especially in the prefrontal cortex, cingulate cortex, and hippocampus in patients with MCI (17). Moreover, acupuncture was found to have modulatory effects on various regions of the brain in patients with MCI in a regional homogeneity-based metaanalysis (18).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted on the efficacy of acupuncture for MCI; however, the methodological quality of these studies has been insufficient in providing convincing evidence (12)(13)(14)(15)(16)(17)(18). Our manuscript describes the protocol for a rigorously designed clinical study that aims to explore the effects of acupuncture on MCI.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the mechanisms of acupuncture have shown that acupuncture can affect brain activity and have long-lasting and significant effects on neural functions ( 14 ). As the number of clinical trials using acupuncture to treat PI continues to increase, a number of studies have confirmed the hypothesis that the activity of specific brain areas was related to sleep and shown that acupuncture could alter these regions ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%